Italian Attempts to Encourage Population Growth - Glass, D. V. (Review of Economic Studies, 1936)
Journal Article Italian Attempts to Encourage Population Growth Get access D. V. Glass D. V. Glass London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 106–119, https://doi.org/10.2307/2967501 Published: 01 February 1936